Skip to main content

Advertisement

Table 4 Transformation rules for τ (for targets) and π (for policies) for decision

From: A framework for the extended evaluation of ABAC policies

τ((a,v)) = \(\bigwedge \{\neg a_{v^{\prime }} \mid v^{\prime }\in \mathcal {V}_{\mathcal {A}}\}\)
τt1) = τ(t1)
\(\tau _{\bot }(\mathop {\sim } t_{1})\) = false
τ(E1(t1)) = τ1(t1)
τ(t1 t2) = (τ(t1)¬τ0(t2))(τ(t2)¬τ0(t1))
τ(t1t2) = τ(t1)τ(t2)
\(\tau _{\bot }(t_{1} \mathbin {\vartriangle } t_{2})\) = τ(t1)τ(t2)
τ(t1 t2) = (τ(t1)¬τ1(t2))(τ(t2)¬τ1(t1))
τ(t1t2) = τ(t1)τ(t2)
\(\tau _{\bot }(t_{1} \triangledown t_{2})\) = τ(t1)τ(t2)
π(1) = false
π(0) = false
π((t,p1)) = τ0(t)τ(t)(τ1(t)π(p1))
πp1) = π(p1)
\(\pi _{\bot }(\mathop {\sim } p_{1})\) = false
π(E1(p1)) = π1(p1)
π(p1 p2) = (π(p1)¬π0(p2))(π(p2)¬π0(p1))
π(p1p2) = π(p1)π(p2)
\(\pi _{\bot }(p_{1} \mathbin {\vartriangle } p_{2})\) = π(p1)π(p2)
π(p1 p2) = (π(p1)¬π1(p2))(π(p2)¬π1(p1))
π(p1p2) = π(p1)π(p2)
\(\pi _{\bot }(p_{1} \triangledown p_{2})\) = π(p1)π(p2)